2004
DOI: 10.1023/b:ddas.0000043368.73042.b0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Autonomic Neuropathy Are More Likely to Develop Hepatic Encephalopathy

Abstract: Autonomic neuropathy (AN) is common in patients with chronic liver disease. For hitherto unknown reasons, in longitudinal studies, the presence of AN has been found to be an independent predictor of mortality in patients with cirrhosis. We hypothesized that patients with AN are more likely to develop hepatic encephalopathy (HE) due to prologed intestinal transit time. In this study, we examined the incidence of new-onset HE in patients with and without AN. Seventy-two patients (Child A/B/C = 35/31/6) without e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Its presence may lead to prolongation of gastrointestinal transit time, small bowel bacterial overgrowth, bacterial translocation and endotoxemia, all of which may predispose to hepatic encephalopathy. Indeed, Maheshwari and colleagues (33) reported that patients with cirrhosis and evidence of an autonomic neuropathy are more likely to develop hepatic encephalopathy than those without. They did not, however, objectively quantify their patients' neuropsychiatric status.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence may lead to prolongation of gastrointestinal transit time, small bowel bacterial overgrowth, bacterial translocation and endotoxemia, all of which may predispose to hepatic encephalopathy. Indeed, Maheshwari and colleagues (33) reported that patients with cirrhosis and evidence of an autonomic neuropathy are more likely to develop hepatic encephalopathy than those without. They did not, however, objectively quantify their patients' neuropsychiatric status.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic dysfunction is also common in diabetics and it has been associated with delayed orocecal transit in these patients (36, 37). Autonomic dysfunction has been proposed to be a predictor of delayed orocecal transit (38) and development of HE in patients with cirrhosis (39). Thus, diabetes might be an additional risk factor for development of autonomic dysfunction and thereby delayed orocecal transit and HE in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Maheshwari and Thuluvath have shown that the presence of autonomic neuropathy was an independent predictor of delayed OCTT in patients with cirrhosis [40]. In a retrospective longitudinal study, cirrhotic patients with autonomic dysfunction were found to have a higher incidence of new onset of hepatic encephalopathy [41]. Second, metabolic derangements in cirrhotic patients as a consequence of porto-systemic venous shunting secondary to portal hypertension may be responsible for delayed OCTT [42].…”
Section: Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%